Entrepreneurship education and entrepreneurial interest among students - Burhanudin, Moch Aziz; Sojanah, Janah; Utama, Dian Herdiana (Journal of Research in Instructional, 2025)
The purpose of this study is to investigate how entrepreneurship education influences Indonesian high school students' desire to start their own businesses and to determine the elements that encourage and inhibit this desire. The research sample consisted of 150 students randomly selected from one high school. The research employed a survey with a questionnaire, and the study's data were evaluated by multiple linear regression. The results showed that interest in entrepreneurship increased significantly through entrepreneurship education with a coefficient of 0.50 (p < 0.0001). Family support, practical experience, and positive attitudes towards risk that significantly influence the desire to start a business. with coefficients of 0.20, 0.30, and 0.15, respectively. The main inhibiting factors include lack of family support and practical experience while supporting factors include relevant curriculum and support from teachers. These findings are in line with the theory of planned behavior and experiential learning theory which emphasize the importance of practical education and social support.